On a Fossil Lotus (Nelumbo nucifera, Gartn.) from Kashmir, with a Note on the History of the Genus - Puri, G. S. (Indian Forester, 1950)
A fossil leaf fragment of Nelumbo nucifera is described from the Upper Ningal valley at an altitude of 9,000 ft., Pir Panjal, Kashmir. This species at the present time, does not occur above the altitude of 5,200 ft. in the valley. The past and present dist ribution of the genus shows that Nelumbo was widespread in Europe dning the Tertiary, while it is now absent from t his region.